2019
DOI: 10.3746/pnf.2019.24.4.381
|View full text |Cite
|
Sign up to set email alerts
|

The Galohgor Nutraceutical Cookies Effects on β-Carotene Serum and Oxidative Stress of Postpartum Mothers

Abstract: The aim of the present study was to analyze the galohgor nutraceutical cookies effects on β-carotene serum levels and oxidative stress of postpartum mothers. To this end, a post-controlled experiment was carried out. Nineteen subjects were recruited to receive 40 g of galohgor cookies (GC) or control cookies (CC) daily for 14 days. Analysis of covariance was applied to assess the effect of the intervention. The results showed that β-carotene serum concentrations were significantly higher in the GC group compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…This biological activity reduces oxidative stress and increases IGF-1 expression. It can be seen from the other parts of this study that reported by Ma'rifah et al 22 and showed that Galohgor cookies reduced malondialdehyde levels in postpartum mothers. The high β-carotene content in Galohgor was thought to underlie the mechanism.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This biological activity reduces oxidative stress and increases IGF-1 expression. It can be seen from the other parts of this study that reported by Ma'rifah et al 22 and showed that Galohgor cookies reduced malondialdehyde levels in postpartum mothers. The high β-carotene content in Galohgor was thought to underlie the mechanism.…”
Section: Resultssupporting
confidence: 72%
“…16,18,21 . Our recent study showed that Galohgor cookies reduced oxidative stress in postpartum mothers 22 . However, its effect on early development had not been studied yet.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, oxidative stress promoted apoptosis of CD4-positive cells (20), and decrease in the number of CD4-positive cells in peripheral blood suppressed cell-mediated as well as humoral immunity (21,22). In human studies, oral beta-caro- tene supplementation reduced oxidative stress in peripheral blood (5,6), and stimulated proliferation of lymphocytes (7,8). Decrease in serum beta-carotene concentration was associated with the development of respiratory and digestive diseases (23).…”
Section: Resultsmentioning
confidence: 99%
“…Beta-carotene plays an important role as an antioxidant inside the body for maintaining the stability of biological membranes (4). Many researches of human and animal supplementation with beta-carotene have reported reduction of oxidative stress and improvements of immunity (5)(6)(7)(8)(9)(10). In particular, many human and animal researches of oral beta-carotene supplementation reported improvement of the peripheral blood leukocyte population (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The mechanism of galohgor effect on increasing breast milk production has been elaborated by several studies that compromised each other. According to Roosita et al 5) and Ma'rifah et al 19) β-carotene is the most carotenoid compound present in galohgor nutraceuticals.…”
Section: Discussionmentioning
confidence: 99%